Study of Senyumanis web-based application impact on dental behaviour and glycaemic control among diabetes patients during COVID-19 pandemic - M Abd Rani, Sarah Liyana; Abdul Aziz, Aznida Firzah; Said, Abdul Hadi; Rani, Haslina; Hamat, Afendi; Zulkiflee, Nurul Syeefa; Mohd Dom, Tuti Ningseh (Community Health Society Malaysia (CHSM), 2024)
Background: Diabetes mellitus (DM) and periodontal disease share a bidirectional relationship as chronic non-communicable conditions. However, limited awareness of this connection in Malaysia hampers patient empowerment, self-care practices, and glycaemic control. Additionally, inadequate coordination between primary medical and dental services exacerbates these challenges. This study investigates the impact of oral health awareness on adults with DM receiving conventional care and Senyumanis© at university-based primary medical clinics in Malaysia.